A No-Excuse Approach to Transitional Justice: Reparations As Tools of Extraordinary Justice - David C. Gray (Washington University Law Review, 2010)
It is sometimes the case that a debate goes off the rails so early that riders assume the rough country around them is the natural backdrop for their travels. That is certainly true in the debate over reparations in transitions to democracy. Reparations traditionally are understood as material or symbolic awards to victims of an abusive regime granted outside of a legal process. While some reparations claims succeed — such as those made by Americans of Japanese descent interned during World War II and those made by European Jews against Germany after World War II — most do not. The principal culprits in these failures are objections that reflect commitments to “ethical individualism.” By way of response, some advocates attempt to put reparations back on course by appealing to theories of collective responsibility. Where put strongly, these theories suffer from basic conceptual deficits. Weaker versions, such as theories based on moral taint and related efforts that seek atonement or reconciliation, turn on moral sentiments, such as regret, and therefore cannot give rise to objective and externally enforceable duties of repair. More creative solutions, such as approaches pursuing “restorative justice,” have some intuitive appeal but want for theoretical clarity and therefore fail to provide persuasive practical guidance. This Article proposes a new approach. Rather than conceiving of reparations as solely retrospective, which implicates knotty issues of responsibility, or solely prospective, which raises problems of enforceability and political practicality, this Article argues that reparations are Janus-faced. In keeping with a larger project arguing that transitional justice is not just a special case of ordinary justice, this Article suggests treating transitions as liminal moments and contends that reparations ought to reflect the extraordinary conditions implied by this temporal status “betwixt and between” an abusive past and a future committed to democracy, human rights, and the rule of law.
Keywords: Transitional justice; Reparations for historical injustices; Human rights; Restitution; Atrocities